Achievement goal modification effects on student self-efficacy and mathematical thinking skills - Joaquin, Ma. Nympha Beltran (2007)
Critical thinking and creative thinking are considered higher order thinking skills (HOTS). The study analyzed the effects of modifying achievement goals on student self-efficacy and mathematical thinking skills. Two types of achievement goal modifications (mastery-goal enhancement and competitive goal enhancement) were investigated. Implications of the results of the study on the multiple goals perspective of the proposed revised achievement goal theory were likewise discussed. A pretest-posttest quasi-experimental research design was used. A total of 149 high school freshmen belonging to three intact classes in a typical public school in Marikina composed the subjects. Results showed that modifying student achievement goals was effective in enhancing the students' target goals and developing among them higher-order thinking skills in mathematics.
Thesis (Ph.D. Mathematics Education)--University of the Philippines, Diliman.
Best dissertation.
Keywords: Mathematics -- Study and teaching (Secondary) -- Philippines -- Marikina City; Mathematical ability -- Testing; Critical thinking -- Philippines -- Marikina City; Self-efficacy -- Philippines -- Marikina City; High school students -- Philippines -- Marikina City